2013
DOI: 10.4161/psb.24097
|View full text |Cite
|
Sign up to set email alerts
|

GmWRKY53, a water- and salt-inducible soybean gene for rapid dissection of regulatory elements in BY-2 cell culture

Abstract: Among abiotic stress conditions, drought is the main culprit that causes huge crop losses worldwide. Therefore, engineering drought tolerance in plants is of major economic importance. Many of the experimental systems that are used in attempts to improve drought tolerance, for example the generation of transgenic plants, are time consuming. For this reason, systems of reduced complexity that allows rapid screening of genes and promoters for potential use in projects aimed at improving drought tolerance are des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…GmWRKY53 is fully consistent with not only the identity of the interacting proteins (VQ) but also the large number of interactors from this family (19).…”
Section: Group Iic and Group I Wrky Transcription Factors Our Data Omentioning
confidence: 70%
See 2 more Smart Citations
“…GmWRKY53 is fully consistent with not only the identity of the interacting proteins (VQ) but also the large number of interactors from this family (19).…”
Section: Group Iic and Group I Wrky Transcription Factors Our Data Omentioning
confidence: 70%
“…GmWRKY53 is up-regulated at the mRNA level as a response to water stress, 19 salt, 18 and Fusarium virguliforme infection. 20 This suggests that GmWRKY53 is part of several stressrelated signalling webs including biotic and abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-fusion construct pMDC43 was used as a control. Here, the tobacco cell system as a model system was selected to study subcellular localization of OsUbc13 for its potential advantages over other cell cultures such as highly synchronized growth rate, high transformation efficiency, and easy monitoring and analysis (Geelen and Inzé, 2001;Tripathi et al, 2013). The data revealed that OsUbc13 was probably localized in the plasma The detection was performed three times and the data were presented as mean±standard deviation (SD).…”
Section: Localization Of Osubc13 In the Plasma And Nuclear Membranesmentioning
confidence: 99%